Beispiel Nr: 15
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1 x +2 y =-4\\ -1 x +2 y = 5 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad 1 x +2 y =-4\\ II \qquad -1 x +2 y = 5 \\ I \qquad 1 x +2 y =-4 \qquad / \cdot\left(-1\right)\\ II \qquad -1 x +2 y = 5 \qquad / \cdot\left(-1\right)\\ I \qquad -1 x -2 y =4\\ II \qquad 1 x -2 y = -5 \\ \text{I + II}\\ I \qquad -1 x +1 x-2 y -2 y =4 -5\\ -4 y = -1 \qquad /:\left(-4\right) \\ y = \frac{-1}{-4} \\ y=\frac{1}{4} \\ \text{y in I}\\ I \qquad 1 x +2\cdot \frac{1}{4} =-4 \\ 1 x +\frac{1}{2} =-4 \qquad / -\frac{1}{2} \\ 1 x =-4 -\frac{1}{2} \\ 1 x =-4\frac{1}{2} \qquad / :1 \\ x = \frac{-4\frac{1}{2}}{1} \\ x=-4\frac{1}{2} \\ L=\{-4\frac{1}{2}/\frac{1}{4}\} \end{array} & \begin{array}{l} \\I \qquad 1 x +2 y =-4\\ II \qquad -1 x +2 y = 5 \\ I \qquad 1 x +2 y =-4 \qquad / \cdot1\\ II \qquad -1 x +2 y = 5 \qquad / \cdot\left(-1\right)\\ I \qquad 1 x +2 y =-4\\ II \qquad 1 x -2 y = -5 \\ \text{I + II}\\ I \qquad 1 x +1 x+2 y -2 y =-4 -5\\ 2 x = -9 \qquad /:2 \\ x = \frac{-9}{2} \\ x=-4\frac{1}{2} \\ \text{x in I}\\ I \qquad 1 \cdot \left(-4\frac{1}{2}\right) +2y =-4 \\ 2 y -4\frac{1}{2} =-4 \qquad / +4\frac{1}{2} \\ 2 y =-4 +4\frac{1}{2} \\ 2 y =\frac{1}{2} \qquad / :2 \\ y = \frac{\frac{1}{2}}{2} \\ y=\frac{1}{4} \\ L=\{-4\frac{1}{2}/\frac{1}{4}\} \end{array} \end{array} $